АНАЛІЗ СУЧАСНОГО СТАНУ ВИКЛАДАННЯ ФІЗИКИ В ТЕХНІЧНИХ УНІВЕРСИТЕТАХ УКРАЇНИ - Іщенко, Руслан (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У роботі проведено аналіз сучасного стану викладання курсу загальної фізики студентам технічних університетів України. Встановлено, що негативно впливають на якість фізичної освіти наступні чинники: втрата престижу інженерно-технічної освіти; низький рівень знань студентів з курсу фізики загальноосвітньої школи та відсутність досвіду самостійної роботи; систематичне скорочення кількості годин, особливо аудиторних, що виділяються на вивчення загального курсу фізики у технічних університетах; застарілість обладнання лабораторних практикумів з фізики. В работе проведен анализ современного состояния преподавания курса общей физики студентам технических университетов Украины. Установлено, что негативно влияют на качество физического образования следующие факторы: потеря престижа инженерно-технического образования; низкий уровень знаний студентов по курсу физики обще-образовательной школы и отсутствие опыта самостоятельной работы; систематическое сокращение количества часов, особенно аудиторных, выделяемых на изучение общего курса физики в технических университетах; устарелость оборудования лабораторных практикумов по физике. In this work the analysis of the current state of teaching of general physics to students of technical universities in Ukraine is performed. It is established that one of the main factors negatively affecting the quality of physics education in these universities is a systematic reduction of the number of hours, especially class hours, devoted to the study of physics. The lack of hours leads to the fact that the course of physics is unsystematic and incomplete. It is concluded that with such number of hours it is quite difficult even for a diligent student to organize and systematize his or her knowledge. It is also revealed that the following factors negatively affect the level of knowledge in physics of students of technical universities: the loss of prestige of engineering education in comparison with legal and economic education; low level of students knowledge of physics of school and the lack of experience of independent work; obsolete equipment for laboratory works in physics.